2020
DOI: 10.1186/s40561-019-0113-2
|View full text |Cite
|
Sign up to set email alerts
|

Accessibility within open educational resources and practices for disabled learners: a systematic literature review

Abstract: The number of disabled students is rapidly increasing worldwide, but many schools and universities have failed to keep up with their learning needs. Consequently, large numbers of disabled students are dropping out of school or university. Open Educational Resources (OER) and Open Educational Practices (OEP) contain several relevant features, including the possibility of reusing and remixing, which have led researchers to consider using OER and OEP to facilitate meeting the needs of disabled and functional-div… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
34
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 85 publications
(45 citation statements)
references
References 35 publications
0
34
0
Order By: Relevance
“…The term "Open Educational Resources" (OER) was first coined at UNESCO's 2002 Forum on Open Courseware, and it was recently defined by UNESCO [1] as "learning, teaching and research materials in any format and medium that reside in the public domain or are under copyright that have been released under an open license, that permit no-cost access, re-use, re-purpose, adaptation and redistribution by others." Several research studies have highlighted that OER have several advantages, as they facilitate knowledge sharing, reduce learning costs, and ensure inclusive learning [2,3]. Due to these advantages, several universities have started adopting OER worldwide.…”
Section: Open Educational Practicesmentioning
confidence: 99%
See 2 more Smart Citations
“…The term "Open Educational Resources" (OER) was first coined at UNESCO's 2002 Forum on Open Courseware, and it was recently defined by UNESCO [1] as "learning, teaching and research materials in any format and medium that reside in the public domain or are under copyright that have been released under an open license, that permit no-cost access, re-use, re-purpose, adaptation and redistribution by others." Several research studies have highlighted that OER have several advantages, as they facilitate knowledge sharing, reduce learning costs, and ensure inclusive learning [2,3]. Due to these advantages, several universities have started adopting OER worldwide.…”
Section: Open Educational Practicesmentioning
confidence: 99%
“…For example, teachers can enhance learners' engagement in open collaboration via technology, such as social networks. [2,3]. Due to these advantages, several universities have started adopting OER worldwide.…”
Section: Open Educational Practicesmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, to increase accessibility to education, ALECSO in collaboration with the secretary Clinton launched in 2013 . Besides, despite the growing number of OER (Hoosen & Butcher, 2019) and the policy attention devoted to OER accessibility, as demonstrated by the presence of guidelines to increase the accessibility of OER within the Ljubljana OER action Action Plan (UNESCO, 2017a, b), the extent to which OER are actually accessible is currently being questioned (Zhang et al, 2020). This is further seen in the Arab region where 68% of the participants reported that there is no OER for learners with disabilities.…”
Section: Oer Accessibilitymentioning
confidence: 99%
“…This is further seen in the Arab region where 68% of the participants reported that there is no OER for learners with disabilities. Particularly, from a literature review conducted by Zhang et al (2020) about OER and disability, only one study is found from Tunisia which discussed the accessibility of MOOCs for learners with disabilities, conducted by Brahim, Khribi, and Jemni (2017). Therefore, much attention should be put to provide accessible OER for learners with disabilities.…”
Section: Oer Accessibilitymentioning
confidence: 99%